In Vivo Assessment of Choroid in Diabetic Retinopathy by Enhanced Depth Imaging in Spectral Domain Optical Coherence Tomography. Issue 5 (September 2016) - Verma, Amrita; Nagpal, Manish; Mehrotra, Navneet
Abstract : Purpose: The aim of this study was to measure the largest hyporeflective (LHR) lumen in the choroid and subfoveal choroidal thickness (SFCT) in patients with diabetic retinopathy (DR) and in control subjects using enhanced depth imaging (EDI) spectral domain optical coherence tomography (SD-OCT). Design: This was a prospective, cross-sectional study. Methods: This was a study of 240 eyes of DR patients (n = 120) and control subjects (n = 120) matched for age, sex, and refractive error. The LHR lumens of the choroidal vessels and SFCT were measured by EDI SD-OCT. Further intergroup classification into nonproliferative and proliferative DR, with or without macular edema, was done. Results: The mean diameter of the LHR lumen in DR patients (139.24 ± 35.53 μm) was significantly smaller ( P < 0.01) than in control subjects (186.37 ± 26.43 μm). The mean SFCT was also significantly less ( P < 0.01) in patients with diabetes (277.15 ± 32.24 μm) as compared with control subjects (313.68 ± 25.13 μm). There was no significant intergroup variation. Conclusions: Patients with DR showed smaller LHR lumen and SFCT as compared with control eyes. In vivo assessment of the choroid in DR is possible using EDI SD-OCT.